BEHÇET HASTALIĞIDA ENDOTEL FONKSİYONLARI VE HOMOSİSTEİN İLİŞKİSİ - BAHŞİ, MUAMMER (Fırat Üniveristesi, 2005)
Behcet's disease, initially described by Hulusi Behcet in 1937, is a chronic, multisystem disorder characterized by recurrent oral and genital ulceration, skin lesions and uveitis. It involves a variety of organs including joints, the gastrointestinal tract, the central nervous system, and the vascular system. The etiologic mechanisms underlying vascular disease in Behcet's syndrome are not well understood. The disease affects individuals of all ages, especially between ages of 20 to 30 years, and both genders. Young age and male gender are associated with more severe disease. The prevalence is higher in Turkey, the Middle East, and Japan than in other countries and the disease is less common in northern Europe and the United State. In our study we use 40 patient with Behcet's Disease and as control group we selected 20 person who has not a serious enfection and cronic disease. In this group 29 unit was active (3 3, 21 ±9,52 age) and the others were inactive (38,73±15,21 age). When we investigate the relation of gender with Behcet's disease we found that, mail gender has a signaficant advantage the patient with active Behcet's disesae than inactive Behcet's disease and control group (P<0,01). Time of illness at the active Behcet's disease was 4,884,88±1,21 years. On the other hand at the inactive Behcet's disesae the year was signaficantly higher 1 1,87±3,12 years (P<0,001). Generally, the patient with the active Behcet's disease has significantly higher homocystein, NO, vitamin B12, folic acid and PAI levels than inactive andcontrol group. But there is no meaningful difference between inactive group and control groups. We observed that, only the plasma ICAM-1 level is significantly higher at two group than control group (P<0,05). But we could not observe a meaningful difference between patient with active and inactive Behcet's disease (P>0,05). As a result; in our study we determined homocysteine, NO, vitamin B12, folic asid and PAİ levels are meaningful higher at active Behcet's disease group than inactive Behcet's disease group and the control group. Therefore we think that, those parameters will be useful at the prognose and diagnose of Behcet's disease but there must be more case number to enter the routine studies. Key words : Behcet's Disease, Endothelial Functions, Homocysteine

Behcet's disease, initially described by Hulusi Behcet in 1937, is a chronic, multisystem disorder characterized by recurrent oral and genital ulceration, skin lesions and uveitis. It involves a variety of organs including joints, the gastrointestinal tract, the central nervous system, and the vascular system. The etiologic mechanisms underlying vascular disease in Behcet's syndrome are not well understood. The disease affects individuals of all ages, especially between ages of 20 to 30 years, and both genders. Young age and male gender are associated with more severe disease. The prevalence is higher in Turkey, the Middle East, and Japan than in other countries and the disease is less common in northern Europe and the United State. In our study we use 40 patient with Behcet's Disease and as control group we selected 20 person who has not a serious enfection and cronic disease. In this group 29 unit was active (3 3, 21 ±9,52 age) and the others were inactive (38,73±15,21 age). When we investigate the relation of gender with Behcet's disease we found that, mail gender has a signaficant advantage the patient with active Behcet's disesae than inactive Behcet's disease and control group (P<0,01). Time of illness at the active Behcet's disease was 4,884,88±1,21 years. On the other hand at the inactive Behcet's disesae the year was signaficantly higher 1 1,87±3,12 years (P<0,001). Generally, the patient with the active Behcet's disease has significantly higher homocystein, NO, vitamin B12, folic acid and PAI levels than inactive andcontrol group. But there is no meaningful difference between inactive group and control groups. We observed that, only the plasma ICAM-1 level is significantly higher at two group than control group (P<0,05). But we could not observe a meaningful difference between patient with active and inactive Behcet's disease (P>0,05). As a result; in our study we determined homocysteine, NO, vitamin B12, folic asid and PAİ levels are meaningful higher at active Behcet's disease group than inactive Behcet's disease group and the control group. Therefore we think that, those parameters will be useful at the prognose and diagnose of Behcet's disease but there must be more case number to enter the routine studies. Key words : Behcet's Disease, Endothelial Functions, Homocysteine
The relation between homocysteine and endothelial functions in Behcet`s disease
Keywords: Biyokimya